The Impacts of Autoimmune Polyendocrinopathy-Candidiasis-Ectodermal Dysplasia (APECED) on the Oral Health of Children and Young People: A Review and Case Report. Issue 1 (May 2022) - Graham, Anna; Javidi, Hanieh; Stern, Melanie; Rogers, Helen J.
Aim: Autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED) is a rare, highly variable disease with significant oral health impacts. The aim of the study is to examine the existing evidence base surrounding the oral health impacts of APECED and consider the wider clinical significance of the condition relevant to the provision of pediatric dental care. Materials and Methods: The evidence surrounding APECED and the oral health impacts obtained from a review of multiple databases was qualitatively summarized in the form of a literature review. A case study was used to illustrate the relevance of literature in caring patients with APECED. Results: The literature describes a broad range of impacts from APECED, although it is characterized by chronic candidal infection, autoimmune hypoparathyroidism, and Addison's disease. Oral manifestations of APECED appear frequently and can present early. Developmental defects of the teeth affect a large proportion of patients with APECED and together with candidiasis, characterize the key oral manifestations of the disease. An enhanced preventive and minimally invasive approach to oral health care is recommended for these patients in light of the complexities of their medical condition. Conclusion: Patients with APECED require careful multidisciplinary care to ensure that the optimal oral health outcomes are achieved.